A continuous model of a standing human body in vertical vibration - Zhang, Qingwen (Array, 2019)
This paper develops a continuous standing human body model in the vertical vibration based on an anthropomorphic model, two measured natural frequencies of a biomechanics model, and structural dynamics methods. The mass distribution of a standing body is formed using the mass distribution of fifteen body segments in the anthropomorphic model. The axial stiffness of the model is determined based on the best matching to the two natural frequencies of the biomechanics model which were obtained using shaking table tests. Four similar models are assessed using finite element parametric analysis. The best of the four models has seven uniform mass segments with two stiffnesses and the same fundamental natural frequency as that of the biomechanics model, but its second natural frequency is 10% higher. The mode shapes of the continuous model are presented to demonstrate the relative magnitude of vibration throughout the height of the body. Finally the modal mass and stiffness of the continuous model are evaluated, which are related to some simple discrete models.